Postnatal manipulation of Pax6 dosage reverses congenital tissue malformation defects - Gregory-Evans, Cheryl Y.; Wang, Xia; Wasan, Kishor M.; Zhao, Jinying; Metcalfe, Andrew L.; Gregory-Evans, Kevin (The Journal of Clinical Investigation, 2014)
Aniridia is a congenital and progressive panocular condition with poor visual prognosis that is associated with brain, olfactory, and pancreatic abnormalities. Development of aniridia is linked with nonsense mutations that result in paired box 6 (PAX6) haploinsufficiency. Here, we used a mouse model of aniridia to test the hypothesis that manipulation of Pax6 dosage through a mutation-independent nonsense mutation suppression strategy would limit progressive, postnatal damage in the eye. We focused on the nonsense suppression drugs 3-[5-(2-fluorophenyl)-1,2,4-oxadiazol-3-yl]benzoic acid (ataluren) and gentamicin. Remarkably, we demonstrated that nonsense suppression not only inhibited disease progression but also stably reversed corneal, lens, and retinal malformation defects and restored electrical and behavioral responses of the retina. The most successful results were achieved through topical application of the drug formulation START (0.9% sodium chloride, 1% Tween 80, 1% powdered ataluren, 1% carboxymethylcellulose), which was designed to enhance particle dispersion and to increase suspension viscosity. These observations suggest that the eye retains marked developmental plasticity into the postnatal period and remains sensitive to molecular remodeling. Furthermore, these data indicate that other neurological developmental anomalies associated with dosage-sensitive genetic mutations may be reversible through nonsense suppression therapeutics.